Pharmacogenetic effects of “candidate gene complexes” on stroke in the GenHAT study - Sørensen, Izel F. (2014)
OBJECTIVE: The goal of this study was to investigate whether there is a genotype by treatment interaction in patients experiencing stroke and treated with one of three antihypertensive drugs, i.e. chlorthalidone, amlodipine and lisinopril. METHODS: A population of 436 African Americans and 539 whites that have experienced stroke in the GenHAT study were genotyped for 768 single nucleotide polymorphisms in 280 candidate genes. To detect a genotype by treatment interaction we used the Pearson's chi-square test to assess if the genotype frequencies differed at the single SNP level for the three drug treatment groups. From these single SNP analyses we derived a summary statistic for the degree of association at the gene and gene complex levels. This was done by grouping SNPs using information on gene locations and defining gene complexes based on protein-protein interactions. To assess the statistical significance of the observed test statistic we derived an empirical p-value by simulating data under the null hypothesis. RESULTS: We found that, in patients that have experienced stroke, there is a significant genetic difference between hypertension drug treatment groups. In African Americans SNP rs12143842 showed significant association (p < 0.001) with drug treatment. At gene-level HNRNPA1P4 and NOS1AP in African Americans and PRICKLE1 and NINJ2 in non-Hispanic whites were significantly associated (p < 0.01) to drug treatment, while none of the gene-complexes tested showed significance. CONCLUSIONS: Based on the genetic differences between drug treatment groups, we conclude that there may be an interaction between certain genotypes and antihypertensive treatment in stroke patients. This needs to be replicated in other studies.